The Effect of Interval Training on Increasing VO2max in Freestyle Swimming Athletes - Akmal Maulana Azzumar; Komarudin; Gafur Ammar Santoso; Mulyana (Universitas Negeri Semarang, 2025)
Swimming is one of the water sports that is already popular among the public, many components are needed to maximize swimming skills, one of which is aerobic endurance VO2MAX. This study aims to examine the effect of interval training on increasing VO2MAX of freestyle swimmers. This research method uses an experimental method with a One Group PreTest PostTest Design design involving 10 freestyle swimmers from the Water Speed Aquatic Club. Sample selection uses a Purposive Sampling technique, with 12 treatments. The instrument used to collect VO2MAX data is the Aerobic Step Test 5 x 200 meters, this instrument is applied before and after using a paired sample T-test. Based on the results of data processing spss, it shows that the Sig. (2-tailed) value is 0.000 <0.05. The results of the pretest-posttest and the overall difference in athletes obtained a pretest score of 58.593 then an increase in the posttest with a value of 61,412 with an average value of 57.44. So it is concluded that there is an effect of interval training on increasing the VO2MAX of freestyle swimming athletes.